2015
DOI: 10.1371/journal.pone.0117026
|View full text |Cite|
|
Sign up to set email alerts
|

Relative Abundance of and Composition within Fungal Orders Differ between Cheatgrass (Bromus tectorum) and Sagebrush (Artemisia tridentata)-Associated Soils

Abstract: Nonnative Bromus tectorum (cheatgrass) is decimating sagebrush steppe, one of the largest ecosystems in the Western United States, and is causing regional-scale shifts in the predominant plant-fungal interactions. Sagebrush, a native perennial, hosts arbuscular mycorrhizal fungi (AMF), whereas cheatgrass, a winter annual, is a relatively poor host of AMF. This shift is likely intertwined with decreased carbon (C)-sequestration in cheatgrass-invaded soils and alterations in overall soil fungal community composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
3
29
1
Order By: Relevance
“…The gradients of these soil chemical parameters across soil depth profiles also differ between the two vegetation types (Weber et al, 2015). As previously noted, such chemical gradients have the ability to alter microbial community structure and composition with soil depth (e.g.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The gradients of these soil chemical parameters across soil depth profiles also differ between the two vegetation types (Weber et al, 2015). As previously noted, such chemical gradients have the ability to alter microbial community structure and composition with soil depth (e.g.…”
Section: Introductionmentioning
confidence: 82%
“…Sagebrush also provides a habitat for unique assemblages of microorganisms in the form of biological crusts on the soil surface (Belnap, 1994) and in sub-surface soils (Weber et al, 2015). However, previous studies have demonstrated that cheatgrass invasion of aridland ecosystems can alter soil microbial community composition and structure as well as rates of microbially-mediated nutrient cycling processes (D'Antonio and Vitousek, 1992;Evans et al, 2001;Rau et al, 2011;Wisdom et al, 2005;Norton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations